2011
DOI: 10.1111/j.1471-0528.2011.03064.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro myometrial contractility reflects indication for caesarean section

Abstract: These findings suggest that the myometrium contracts with greater force in women who have a caesarean section for fetal distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous work from our group has shown that in vitro myometrial contractility can reflect in vivo clinical activity and labour outcome [10], [11]. The question therefore arises whether in vitro activity of myometrium from twins is different to that of singletons, making it a useful model for mechanistic studies focussed on risk of preterm labour.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from our group has shown that in vitro myometrial contractility can reflect in vivo clinical activity and labour outcome [10], [11]. The question therefore arises whether in vitro activity of myometrium from twins is different to that of singletons, making it a useful model for mechanistic studies focussed on risk of preterm labour.…”
Section: Introductionmentioning
confidence: 99%
“…11 One reason for insufficient progression of labor is weak contractility of the uterus. 12,13 Low uterine contractility can also delay the initiation of labor, 14 another risky situation for the mother and fetus. 15 Insufficient uterine contractility can also cause postpartum hemorrhage, 16 the leading cause of maternal death.…”
Section: Introductionmentioning
confidence: 99%
“…Other lead compounds currently under development with this assay include retosiban (GSK221149A)38 and nolasiban (data unpublished). These methods have also been used successfully to compare between patient groups39,40,41,42,43,44,45,46,47 and examine for intra-species differences.…”
Section: Introductionmentioning
confidence: 99%